2023
DOI: 10.1039/d2nr05447g
|View full text |Cite
|
Sign up to set email alerts
|

Wearable chemical sensors based on 2D materials for healthcare applications

Abstract: Chemical sensors worn on the body could make possible the continuous, noninvasive, and accurate monitoring of vital human signals, which is necessary for remote health monitoring and telemedicine. Attractive for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 230 publications
0
13
0
Order By: Relevance
“…Secondly, the electron-deciency degree of Co nanosheets is improved under visible irradiation, resulting in greatly decreased H 2 O activation and dissociation energy barrier. 29 Thirdly, the increased NH 3 BH 3 hydrolysis rate over Co/Cr 2 O 3 -E-0.5 under visible irradiation further conform the effect of Cr 2 O 3 on activity of catalyst. Notably, the activity of Co/Cr 2 O 3 -E-0.5 with TOF 95.7 min −1 is lower than Co/Cr 2 O 3 -F-0.5.…”
Section: Photocatalytic Performancementioning
confidence: 66%
See 1 more Smart Citation
“…Secondly, the electron-deciency degree of Co nanosheets is improved under visible irradiation, resulting in greatly decreased H 2 O activation and dissociation energy barrier. 29 Thirdly, the increased NH 3 BH 3 hydrolysis rate over Co/Cr 2 O 3 -E-0.5 under visible irradiation further conform the effect of Cr 2 O 3 on activity of catalyst. Notably, the activity of Co/Cr 2 O 3 -E-0.5 with TOF 95.7 min −1 is lower than Co/Cr 2 O 3 -F-0.5.…”
Section: Photocatalytic Performancementioning
confidence: 66%
“…Importantly, electron-decient Co species can decrease H 2 O activation and dissociation energy barriers (rate-determining step in NH 3 BH 3 hydrolysis) and then accelerate the rate of reaction. 29 To date, the design of catalyst has mainly focused on tuning electronic structures of active metal, while neglects catalyst wettability. The appropriate wettability of a catalyst can signicantly enhance the adsorption and transfer of reactants, resulting in enhancement activity.…”
Section: Introductionmentioning
confidence: 99%
“…The detection mechanism of strain sensor is greatly varied depending on the response signals, mostly electrical or optical signals. 5,21 Along with the development of materials science, strain or pressure sensors using nanomaterials have gained significant attention in recent years due to their remarkable characteristics and potential applications in various fields. These sensors utilize the unique characteristics of nanomaterials to detect and measure mechanical forces, enabling precise monitoring and control in diverse industries such as healthcare, 22 robotics, 23 aerospace, 23 etc.…”
Section: 𝜀 = F∕aementioning
confidence: 99%
“…In most of the cases, different kinds of signals like physical, chemical, or biological signals are converted into electrical signals, which are perceived as a universal form to be processed. 5,6 Sensors are classified depending on the applications, input signal, and transducing mechanism, in general, sensors help to solve many problems related to human life, which could be accounted to human prostheses, 7 stress imaging, 8 real-time health monitoring, 9 clinical medicine, humancomputer interaction 10 and other fields. Thus, strain and pressure sensors have brought huge interest of the research communities with a wide range of applications as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) materials have attracted widespread interest over the past decade because of their distinctive and versatile properties. − Successful proofs of concept for their implementation have been demonstrated in various fields, including electronics, optoelectronics, photonics, sensors, and memory devices. − Among the 2D materials, the semiconducting transition metal dichalcogenides (TMDs) received significant attention owing to their tunable band gap and excellent electronic and optical properties, which are highly promising for future application in nanoelectronic devices. − The semiconducting 2D TMD materials molybdenum disulfide (MoS 2 ) and tungsten disulfide (WS 2 ) are channel materials of high potential for implementation in ultimately scaled electronic devices because of their atomic-scale thickness. Moreover, the surface of ideal 2D crystals lacks dangling bonds.…”
mentioning
confidence: 99%